Determining research priorities for clinician‐initiated trials in infectious diseases. Issue 5 (18th March 2013) - Paterson, David L
Abstract: Objectives: To determine research priorities of infectious diseases physicians for clinician‐initiated randomised controlled trials (RCTs). Design, setting and participants: Online survey of infectious diseases physicians in Australia and New Zealand. Main outcome measures: Research priorities for, and perceived barriers to, clinician‐initiated RCTs. Results: 122/550 infectious diseases physicians (22%) responded to the survey. The five highest ranked proposals for clinician‐initiated RCTs were in the areas of prosthetic joint infections, septic arthritis and osteomyelitis of native joints, Staphylococcus aureus bloodstream infections, diabetic foot infections and the treatment of serious multiresistant, gram‐negative bacterial infections. Lack of funding was the most important perceived barrier to participation in clinician‐initiated RCTs. Conclusions: The research focus of infectious diseases physicians — optimal treatment of commonly encountered serious infections — highlights a lack of well conducted RCTs in this area.